Lung cancer screening: targeting the hard to reach—a review - Van Hal, Guido (Transl Lung Cancer Res, 2021)
Lung cancer (LC) is the leading cause of cancer death in the USA for both men and women, and also worldwide, it is the commonest cause of cancer death. The five-year survival rate for LC depends on the stage at which it is diagnosed. It is over 50% for cases detected in a localized stage but when the disease has spread to other organs, the five-year survival rate is only 5%. Unfortunately, only 16% of LC cases are diagnosed at an early stage. In 2013, the US Preventive Services Task Force (USPSTF) recommended annual LC screening with low dose chest computed tomography (CT) in adults aged 55 to 80 years who have a 30 pack-year smoking history and currently smoke or have quit within the past 15 years, based on the evidence from the National Lung Screening Trial (NLST) in the USA. When it comes to recruiting the target group for lung cancer screening (LCS), there are several barriers to overcome, such as whom exactly to include, where to find the target group, how to convince the target to participate or how to attract participants from all socioeconomic groups. The aim of this review is to find out what is already known about how the target group for LCS can be contacted and how participation can be improved, since uptake is a key issue in every (cancer) screening program. A review of the literature was conducted using ‘lung cancer screening and participation and uptake’ as search string. We searched in Web of Science and PubMed for reviews, systematic reviews and articles, published between 2015 and 2020. Compared to the target groups for screening in the long-running cancer screening programs of breast, cervical and colorectal cancer, there are several additional obstacles regarding defining, locating and recruiting of the target group for LCS. Shared decision-making is crucial when we want to reach the hard to reach for LCS and it should be improved, by educating primary care practitioners about LCS guidelines and providing them with the necessary tools, such as decision aids, to facilitate their job in this respect. Moreover, the information materials should be more tailored to specific groups who participate least.